HDL as a drug and nucleic acid delivery vehicle - Lacko, Andras G.; Sabnis, Nirupama A.; Nagarajan, Bhavani; McConathy, Walter J. (Frontiers in Pharmacology, 2015)
This review is intended to evaluate the research findings and potential clinical applications of drug transport systems, developed based on the concepts of the structure/function and physiological role(s) of high density lipoprotein=type nanoparticles. These macromolecules provide targeted transport of cholesteryl esters (a highly lipophilic payload) in their natural/physiological environment. The property of accommodating highly water insoluble constituents in their core region enables HDL type nanoparticles to effectively transport hydrophobic drugs upon intravenous administration. Even though the application of reconstituted HDL in the treatment of a number of diseases is reviewed, the primary focus is on the application of HDL type drug delivery agents in cancer chemotherapy. The use of both native and synthetic HDL as drug delivery agents are compared to evaluate their respective potentials for commercial and clinical development. The current status and future perspectives for HDL type nanoparticles are discussed, including current obstacles and future applications in therapeutics.